2024
DOI: 10.3233/thc-230059
|View full text |Cite
|
Sign up to set email alerts
|

Dural puncture epidural with 25-G spinal needles versus conventional epidural technique for labor analgesia: A systematic review of randomized controlled trials

Abstract: BACKGROUND: Dural mater is punctured by using a spinal needle without drugs administrated into intrathecal space directly in dural puncture epidural (DPE) analgesia. OBJECTIVE: This study aimed to summarize the evidence of benefits and risks of DPE analgesia with 25-G spinal needles for labor pain relief. METHODS: DPE analgesia with EP analgesia for labor pain relief were systematically searched. The Embase, MEDLINE, Cochrane Central Register of Controlled Trials, Scopus and Web of Science databases were syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…18 A recent metaanalysis demonstrated that the DPE technique with 25G spinal needle offers advantages over the EP technique. 7 These advantages include hastened onset of analgesia, decreased necessity for epidural top-ups, and a reduced occurrence of asymmetric block. 7 Larger size spinal needles (25G) were used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 A recent metaanalysis demonstrated that the DPE technique with 25G spinal needle offers advantages over the EP technique. 7 These advantages include hastened onset of analgesia, decreased necessity for epidural top-ups, and a reduced occurrence of asymmetric block. 7 Larger size spinal needles (25G) were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…7 These advantages include hastened onset of analgesia, decreased necessity for epidural top-ups, and a reduced occurrence of asymmetric block. 7 Larger size spinal needles (25G) were used in our study. We observed higher percentages of adequate analgesia at 8, 12, 14, and 16 minutes after the initial epidural dose in the DPE group, along with a significant shorter median time to adequate analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 9% of mothers can tolerate labor pain ( 9 ). Epidural anesthesia effectively relieves labor pain ( 10 , 11 ). Most studies on epidural anesthesia for labor analgesia have been conducted in areas of normal altitude, e.g., plains.…”
Section: Introductionmentioning
confidence: 99%